Strategi Penyiaran Program “ Selamat Pagi Kabupaten Bogor” untuk Meng - Update Informasi kepada Pendengar: Studi Kasus: Radio Teman 95,3fm - Annory Langga’o; Ameilia Andriani Putri (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This study uses a qualitative method of a descriptive approach with an interpretive paradigm to gain an in-depth understanding of the process of planning, implementing, and evaluating broadcast programs. This research was carried out at the Communication and Information Office of Bogor Regency, Jalan Tegar Beriman Number 1, Pakansari, Cibinong District, Bogor Regency, West Java 16914. The data collection techniques used are direct observation of the broadcast process, in-depth interviews with broadcasters and program managers, and documentation to support the validity of research data. The results of this study show that broadcasting strategies are implemented through content planning that suits the needs of listeners, the implementation of interactive broadcasts involving listeners and routine evaluation to maintain the quality of the information that has been delivered. In addition, the use of digital media as a streaming platform and interaction through social media also supports a wider reach to listeners. The conclusion of the broadcasting strategy implemented by Radio Teman 95.3 FM is considered effective in maintaining listener loyalty and attracting new audiences, so that it can be an example for other local radio stations in facing the current digital media competition.technological optimization, audience engagement, and adaptation to the development of new media.